Reliability of fine needle aspiration and ex tempore biopsy in the diagnosis of salivary glands lesions - Gajanin, Radoslav; Djurdjević, Dejan; Knežević Ušaj, Slavica; Eri, Živka; Ljubojević, Vesna; Karalić, Marinko; Risović, Tatjana (Vojnosanitetski pregled, 2014)
Background/Aim. Interpretation of cytological material obtained by fine needle aspiration (FNA) of salivary glands is one of the most challenging areas in cytopathology. FNA is performed easily, it is minimally invasive, inexpensive, fast, reliable and provides valuable information to clinicians about the nature of the lesion and therapeutic modalities. Ex tempore diagnosis, frozen section (FS) is a diagnostic tool that is essential in determining the modalities of surgical treatment of lesions of the salivary glands. Today this method is used in determining the status of resection margins and infiltration of adjacent anatomical structures. The aim of this study was to present our experiences in the application of FNA and FS in the diagnosis of salivary gland lesions and to determine the sensitivity, specificity, predictive value, and diagnostic reliability of these methods. Methods. The study included 36 patients. In all the patients, cytological analysis was done before surgery and histological analysis of the surgical material. In 23 of the patients the FS diagnostics was done. Then we compared FNA and FS findings with histopathological findings. Results. Correlation of cytological and histological diagnosis showed sensitivity of 83.3%, specificity 96.67%, positive predictive value 83.3%, negative predictive value of 96.77% and diagnostic accuracy of 97.2%. Based on the relationship between FS diagnosis and histopathological diagnosis, the sensitivity was 100%, specificity 96.67%, while positive predictive value and diagnostic accuracy were 100% each. Conclusion. The study confirmed that FNA is a sensitive, reliable diagnostic method for differentiation of lesions of the salivary glands. In cases with no posibility to definite differentiation in FNA samples, and with the need to assess the resection margins and invasion of anatomical structures, it is recommended to use FS diagnostics.